Therapeutic Approaches for Clostridium difficile Infections. Issue 1 (16th February 2018) - Marsh, Jane W.; Curry, Scott R.
Abstract: Metronidazole and vancomycin remain the front‐line therapies for most Clostridium difficile infections (CDI). However, recurrent CDI occurs in ∼25% of patients, causing significant morbidity and mortality and healthcare costs. For this population, traditional antibiotic therapies fail and new treatment options are greatly needed. The US Food and Drug Administration recently approved fidaxomicin for CDI treatment. This narrow‐spectrum antibiotic preserves the normal gut microbiota and shows promise as a treatment for severe and recurrent CDI. Monoclonal antibodies and vaccines directed against toxin are currently in clinical trials and represent alternative, non‐antibiotic therapies. Less traditional therapeutic interventions include bacteriotherapy with non‐toxigenic C. difficile and fecal transplant. This commentary will provide an overview of current and forthcoming CDI therapies. Curr. Protoc. Microbiol . 30:9A.3.1‐9A.3.9. © 2013 by John Wiley & Sons, Inc.